Interdependent Followers Prefer Avoidant Leaders: Followers’ Cultural Orientation Moderates Leaders’ Avoidance Relationships with Followers’ Work Outcomes - Kafetsios, Konstantinos G.; Gruda, Dritjon (Frontiers in Communication, 2018)
Several studies examining leader-follower interaction in Greece, a collectivistic culture, paradoxically find that leaders' emotion suppression-related personality traits (attachment avoidance, emotion suppression, emotion control) have positive effects on followers' emotional and work attitude outcomes. These findings have been explained with reference to followers' implicit cultural schemas, interdependence in particular. Yet, this conjuncture has not been directly tested. The present study directly examined, in a field setting, how followers' independent and interdependent (cultural) self-construal moderates the relationship between leaders' attachment orientation and followers' emotion and satisfaction outcomes at the work place. As hypothesized, leaders' higher avoidance was associated with followers' job satisfaction, group cohesion, and deep acting as well as lower negative affect and loneliness for followers higher on interdependent self-construal. The results underline perceptual processes involved in followers' interdependent self-construal in relation to leaders' emotion suppression-related traits.